Management at the enterprise on the basis of ESG principles in the conditions of sanctions pressure - E. Yu. Vasilyeva; Yu. O. Bakrunov; A. V. Oleynik (Вестник университета)
The principles of ESG in management as the basis of sustainable development of the company, industry and economy in general are considered in the article. The authors deal with the issue, whether the rupture of economic links and financial schemes, as well as the exception of the Russian companies from the international ESG-ratings can lead to refusal of the ESG-principles in management. The features, peculiar to each of the ESG aspects in the conditions of the anti-Russian sanctions in 2022 are considered. The problems and strengths of the Russian companies, the degree of prevalence of the ESG principles among the Russian entrepreneurs are revealed. According to the data of analyst companies, research and polls, the authors conclude, that the enterprises applying the ESG-principles have more chances to recover from the current crisis successfully.